Investigation of Performance on Photovoltaic/Thermal (PV/T) System Using Magnetic Nanofluids - Swese, Ettahır El Hadı Alı Omar; Hançerli̇oğullari, Aybaba (Politeknik Dergisi, 2022)
Photovoltaic/Thermal (PV/T) systems provide hot fluid (usually water) production as well as electrical energy production. In addition, since the overheating of the PV systems is prevented by the heat drawn by the thermal system, the electricity production performance of the PVs increases. Nanofluids are offered as a solution to increase the heat absorbed in the thermal system. The main physical events that lead to a significant improvement in the heat transfer performance of nanofluids can be summarized as follows: (i) The thermal conductivity of the prepared nanofluid increases at certain rates because the thermal conductivity of the solid metal is higher than that of the basic fluid, (ii) The heat transfer surface area increases due to the increase in the thermal conductivity of the fluid, (iii) Increase in the effective thermal capacity of the fluid, (iv) Increase in the thermal conductivity of the fluid and turbulent volume due to high fluid activity. In this study, by using nanofluids obtained by adding 1% Fe2O3, Fe3O4 and NiFe2O4 magnetic nanoparticles by weight to the basic fluid water, a bidirectional performance increase was achieved by increasing the thermal heat transfer of the PV/T system while providing more cooling of the PV system. In the experimental study, a 14% improvement in electricity production was achieved in NiFe2O4 nanofluid by drawing more heat from the heated PV panels by utilizing the high thermal conductivity of nanofluids. Since the amount of heat absorbed in the thermal system is high, an average of 104% temperature (∆T) increase in the hot fluid temperature compared to the base fluid water was obtained in the NiFe2O4 nanofluid.
Keywords: PV/T; nanofluids; magnetic nanoparticles; Fe2O3; Fe3O4; NiFe2O4; Engineering; Mühendislik; PV/T; nanoakuşkan; magnetic nanoparçacıklar; Fe2O3; Fe3O4; NiFe2O4; 7. Clean energy; 6. Clean water